Menerapkan Konsep Logika Fuzzy Dalam Meningkatkan Efisiensi Persediaan Barang Dengan Menggunakan Metode Mamdani - Galih Yudhistira; Pika Aliya Widiastuti; Rahyuni; Tri Hastono (Pusat Riset dan Inovasi Nasional, 2024)
Jars are one of the handicrafts used as a tool to fulfill daily life, and have social, ritual and artistic values. With good prospects to be developed considering the market potential that is increasingly widespread in its use. So that a good promotional strategy is needed to improve the urn product industry. The method used in this research is Fuzzy Logic Mamdani which can overcome uncertainty and complexity of information in decisions. For data collection in this study, namely by survey or asking directly to the urn seller. The objectives of this study include the application of Mamdani calculations, prediction of urn stock, and guidelines for determining the optimal amount of production. From the calculations obtained, demand increased by (0.029), products sold a lot by (0.105) and inventory increased by (0.222).